Fifty shades of Grey - James, E. L. (New York : Vintage, 2012)
When literature student Anastasia Steele is drafted to interview Christian Grey for her campus magazine, she finds him attractive, enigmatic and intimidating. Convinced their meeting went badly, she tries to put Grey out of her mind -- until he happens to turn up at the out- of-town hardware store where she works part-time.
Originally published: Waxahachie, Tex. : Writer's Coffee Shop Publishing House, 2011.
Keywords: College students -- Fiction; Businesspeople -- Fiction; Man-woman relationships -- Fiction; Erotic fiction